The Ethics of Debate in Hadith Perspective: An Analysis of Abū al-Laith al-Samarqandī's Thoughts - Sulton Jordi; Repa Hudan Lisalam; Abdul Fatah (International Tatho Academics, 2024)
This study discusses the ethics of debate in the perspective of hadith by examining the thoughts of Abu Laith al-Samarqandiy in the book Bustān al-ʿĀrifīn. The background of this study focuses on the phenomenon of debate that often leads to hostility and division in society, especially when the debate aims to humiliate, dominate, or seek recognition. Abu Laith al-Samarqandiy emphasized that this attitude deviates from Islamic ethics that promotes unity and prevents stubbornness in arguing. This study uses a qualitative-descriptive method with text analysis to understand the ethical principles of debate in the view of hadith and al-Samarqandiy's thought. The results of the study show that debates aimed at maintaining the ego and bringing down the opponent are reprehensible behavior and even sinful if it results in interference for others. Islam requires a Muslim to avoid debate, even when on the right side, in order to maintain peace and harmony in the community.